Grafts Are Superior to Sutures for Nasal Tip Projection: A Meta‐analysis of Goodes Ratio. (2nd September 2014) - Cole, Eric; Natili, Angelia S.
Abstract : Objectives: (1) Discuss relevant tip projection ratios involved in surgical planning of rhinoplasty. (2) Implement findings of meta‐analysis in cosmetic surgery planning. Methods: Meta‐analysis of journal articles through June 2013. Intervention: Cosmetic rhinoplasty for underprojected tip. Outcome Measurements: Pre‐ and postoperative Goode Ratio in cosmetic rhinoplasty patients. Null hypothesis: None of 3 techniques provides superior tip projection among: suture, internal graft, and external graft. Results: External graft techniques, such as Sheen shield grafting, were found to significantly increase tip projection over suture only techniques. External vs suture: P =. 017. (2) Internal graft techniques, such as columellar strut grafting, approached significance in increased tip projection over suture only technique. Internal vs suture: P =. 053. (3) Internal and external graft techniques did not differ significantly, but external graft techniques displayed a tendency to increase tip projection more. External vs internal: P =. 360. Conclusions: (1) Meta‐analysis of the Goode Ratio has never been reported in the literature. (2) No technique has been proven to have significance in the past. (3) External grafts produce a significant change in nasal tip projection over suturing, and internal grafts approach significance. (4) This research allows the surgeon to rank techniques in order of magnitude of change desired.